The Lithuanian Soviet Nomenclature as an Object and Subject of Control - Ivanauskas, Vilius (Genocidas ir rezistencija, 2012)
The topic of nomenclature in the context of research on the Soviet period is usually associated with the power and influence exerted by a single group in society. While assessing the evolution of the post-Stalin system, the role of a separate ruling stratum rather than that of an individual leader becomes more apparent. Many studies hesitate to call the post-Stalin system totalitarian and secretary-generals of the Communist Party as unilateral leaders. In individual studies, nomenclature, particularly top ranking, is clearly perceived as an acting and influencing subject, capable of subjecting system resources to its articulated aims. However, the discussion of the role of Lithuanian nomenclature as a certain peripheral elite and its relationship with the system shows that it is impossible to treat it only as an acting subject. The interests and management style of the central government determined greater or lesser control of the Soviet republics. So it is interesting to consider which situations would define the Lithuanian Soviet nomenclature itself as an object of control, and in which areas it could express its own interests and be activity. The Soviet institutional environment was saturated with control. Control measures were designed not only to control processes in society; they were also applied to the system of nomenclature itself by applying hierarchical control principles both to the governing political party and lower executive ranks. Information was collected about ideological compliance and participation in the execution of plans. Transgressions recognised to be ideological were assessed most strictly. The tools of control were diverse: in addition to control bodies (people’s control, GLAVLIT, KGB) Communist party structures and ministries had their own divisions responsible for control of the activities of a particular area and even the suitability of people. In addition to routine planned activity, individual influential officials carried out controlling functions and exposed ad hoc cases. It can be stated that the system was essentially saturated with control activities – the same area was controlled by at least 3-4 levels different levels of officials and this obviously stifled the dynamics of any activity. In the late Soviet period, locality as a factor of social environment can be clearly distinguished whereby local representatives of the nomenclature would often reduce the effect of control by replacing the object ‘what and how to control’ with the consensus of higher ranking officials of the nomenclature regarding the areas and leaders to be controlled and possible consequences of control (including penalties for members of the Communist Party). This model complemented institutional regulation and was applied not only to ensure control inside a republic but also in relation to the supervision carried out by the centre. The government of the republic frequently faced hostility from some leaders controlling the manufacturing industry, but except for one incident, it managed to ‘localise’ both local and arriving leaders, thereby creating a certain closed social network of members of the nomenclature of the republic and simultaneously opening more opportunities for higher ranking officials of Lithuanian nomenclature to express their personal interests, assess the situation subjectively, and act in the area of control as a subject rather than an object. The social network of members of the nomenclature of the republic rather actively and using various measures sought to isolate their own circle therefore ensuring not only the integrity of the circle, but also control of the space subordinate to it, while at the same time maintaining good relations with the centre. The top ranking officials of the republic were very keen to maintain the stability of this network and their primary goal was to preserve the routine of governing, given that this status quo was in line with Brezhnev’s governing style.